Upaya Promosi Kesehatan Pendewasaan Usia Perkawinan Oleh Pusat Informasi Konseling Remaja (PIK-R) Ditinjau Dari Teori Precede-Proceed (The Effort of Health Promotion on Maturation of the Marriage Age by Information and Concelling Center for Adolescent (PI - Dina Mei Wahyuningrum; Husni Abdul Gani; Mury Ririanty (Pustaka Kesehatan, 2015)
The result of UNICEF report showed that Indonesia has high percentage on early marriage inthe world, Indonesia was in 37th rank from 63 country. One of district in Jember regency whichhas the highest mark in early marriage is Sukowono district. There were 411 mate whomarriage in early age. The effort to reduce the amount of early marriage was by maturation ofthe age marriage which hold by information and conselling center for adolescent (PIK-R). Theactivity of PIK-R in effort on Maturation of marriage age by giving information, but this activityonly give to the members of PIK-R. It caused most of adolescent didn't know more aboutmaturation of marriage age. The purpose of this research was to know effort of healthpromotion on maturation of the marriage age by PIK-R based precede proceed theory. Thisresearch design used Qualitative research based on the result showed that most of society inSukowono district did early marriage because their parents were match them, so their familygave support to do early marriage. The effort of maturationof the marriage age which washold by PIK-R consist of planning, implementation and evaluation. Planning of PIK-R consistof target determined, content, media, advocacy and regulacy. The implementation of PIK-Rwas hold by giving information to the society about maturation of the marriage age, butevaluation from implementation was not suitable with planning.Keywords : Health promotion on maturation of the age marriage, PIK-R, Precedeproceedtheory.